2021
DOI: 10.1111/and.13957
|View full text |Cite
|
Sign up to set email alerts
|

Assessing online price transparency of sperm cryopreservation across the United States

Abstract: Although the lack of information on the costs and pricing of healthcare services prevails throughout the medical industry, empiric observations have demonstrated that pricing information is even more obscured in the sperm cryopreservation market. Thus, the objectives of our study are to assess and compare online price transparency and the price of sperm cryopreservation across various healthcare settings in the United States. This study examined online pricing published by facilities that have an active regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, a 2020 study found price transparency to be an issue. Of the facilities listing sperm cryopreservation as an available service, only 17.7% had pricing information readily available [71]. Should patients use their cryopreserved tissue to conceive, the cost increases.…”
Section: Financial Barriersmentioning
confidence: 99%
“…Furthermore, a 2020 study found price transparency to be an issue. Of the facilities listing sperm cryopreservation as an available service, only 17.7% had pricing information readily available [71]. Should patients use their cryopreserved tissue to conceive, the cost increases.…”
Section: Financial Barriersmentioning
confidence: 99%
“…Storage and fertility treatments vary in cost across countries. Whereas some countries cover total financial costs through the public health system, other countries have only private health services and thus the financial status of the patient ultimately decides their options [ 14 , 71 , 72 , 73 , 74 ].…”
Section: Introductionmentioning
confidence: 99%